Neighbourhood tobacco retail access and tobacco use susceptibility in young adolescents in urban India. Issue Volume 31:Issue e2(2022) (25th November 2021) - Mistry, Ritesh; Kleinsasser, Michael J; Puntambekar, Namrata; Gupta, Prakash C; McCarthy, William J; Raghunathan, Trivellore; Adhikari, Keyuri; Narake, Sameer; Hsieh, Hsing-Fang; Desai, Maruti; Assari, Shervin; Alberts, Joseph; et al.
Abstract : Background: Neighbourhood tobacco retail access may influence adolescent tobacco use. In India, we examined the association between neighbourhood tobacco retail access and cognitive risks for tobacco use during early adolescence. Methods: In 2019–2020, a population-based sample (n=1759) of adolescents aged 13–15 years was surveyed from 52 neighbourhoods in Mumbai and Kolkata. Neighbourhood tobacco retail access was measured as the frequency of visits to tobacco retailers, mapped tobacco retailer density and perceived tobacco retailer density. We estimated associations between neighbourhood tobacco retail access and cognitive risks for tobacco use (perceived ease of access to tobacco, perceived peer tobacco use and intention to use tobacco). Results: There was high neighbourhood tobacco retail access. Tobacco retailer density was higher in lower income neighbourhoods (p<0.001). Adolescent frequency of tobacco retailer visits was positively associated with cognitive tobacco use risks. Mapped tobacco retailer density was associated with perceived ease of access in Kolkata but not in Mumbai, and it was not associated with perceived peer tobacco use nor intention. Perceived tobacco retailer density was associated with perceived ease of access and perceived peer use, but not with intention. In Kolkata, higher perceived retailer density and frequency of tobacco retailer visits were negatively associated with perceived ease of access. Conclusions: Efforts to reduce neighbourhood tobacco retail access in India may reduce cognitive tobacco use risk factors in young adolescents. The frequency of tobacco retailer visits and perceived tobacco retailer density increased cognitive risks, though there were some exceptions in Kolkata that further research may explain.